Perluasan Makna Kata Doumo dalam Bahasa Jepang - Gandhewa Hening, Eudes Pendar; Sitepu, Melati Br (Journal of Language Education Studies and Applied Linguistics, 2024)
This research delved into the semantic analysis of the word "doumo" in the Japanese language, aiming to understand its evolving meanings in various contexts. By employing qualitative descriptive methods, the study explored the factors influencing the word's semantic shifts and its implications in everyday communication. Through the analysis of data from diverse sources, the study shed light on the nuance’s usage of "doumo" and its significance in Japanese linguistic interactions. The methodology utilized in the research involved collecting and analyzing data from multiple sources to uncover the intricate layers of meaning associated with "doumo." By examining 52 data sentences, the study delved into the semantic and syntactic structures of the word, providing insights into its varied interpretations. The qualitative descriptive approach allowed for a deep exploration of the word's usage, transcending numerical constraints to capture the qualitative essence of its meaning. In conclusion, the study highlighted the dynamic nature of language and the importance of semantics in deciphering linguistic nuances. The findings underscored the significance of context and social factors in shaping the meanings of words like "doumo" in Japanese communication.